An Investigation on the Effects of Climate Change and Variability in the Rainfall of Old Sudan - Abdalla, Abdalla K; Gamri, Tarig El; Saeed, A B (Annals of Arid Zone, 2019)
It was estimated that Old Sudan was facing water stress since the per capitaannual share was 1500 m3. It was evident that rainfall plays a determinant role in thesocio-economic set up of Old Sudan. The study area showed marked variation regardingrainfall distribution since it is almost nil at the extreme north and about 1500 mm at theextreme Southwest. Isohyetal maps for the two climatic eras’ 1941-1970 and 1971-2000showed significant southward displacement. The rainfall of both Khartoum and Fashirshowed a trend of decline whereas, maximum temperatures witnessed an increase. Thetotal annual rainfall data for some meteorological stations, since their inception, weredivided into three eras namely: the period up to 1950, the second half of the 20th centuryand the first ten years of the 21st century. Considering the period of up to 1950 as thebase period a striking reduction was observed. For instance, a reduction of approximately15% was witnessed in the central portion meanwhile it was about 20% in Darfur. Inaddition to that, most locations demonstrated significant further decline during thefirst ten years of the 21st century. On the other hand, the ENSO event proved to exerta determinant role in the variability of the rainfall of old Sudan. Contrary to El Ninothe rainfall during La Nina is found to be above normal. Some adaptive options wererecommended including modernization of irrigation and, adoption of supplementaryirrigation and water harvesting.Key words: Rainfall, ENSO, prediction, socio-economic development, water scarcity,sanitation.